A Child Died of What he Was Treated For, But... - I.V. Bogadelnikov; Ye.A. Kruger; A.V. Bobrysheva; Yu.V. Vyaltseva; A.F. Ilyin; Ye.V. Zdyrko; Ye.S. Ivchenko; E.R. Mazinova (Zaslavsky O.Yu., 2014)
This article describes atypical clinical case of Reye syndrome in 10-year-old girl, appeared on the background of acute enteric infection, and led to death. On the basis of clinical and laboratory data, was well as medical history of the child we performed short differential diagnosis of Reye syndrome, epilepsy and encephalitis, and conditions associated with dysfunction of the nervous system and the liver: fulminant hepatic failure, pancreatic encephalopathy, meningitis, congenital errors of metabolism.